The use of unmanned aerial vehicles for land management - Butenko, E.; Kulakovskii, O. (Land Management, Cadastre and Land Monitoring, 2019)
The article is devoted to a comparative analysis of the use of unmanned aerial vehicles for solving problems of land management. Scientific work highlights the prospects for the use of unmanned aerial systems in the implementation of local monitoring and the need to take into account the possibility of using unmanned aerial systems of various types in making management decisions to ensure their maximum efficiency in the shortest possible time. Given problem is not sufficiently substantiated in the Ukrainian law and this can lead to the complication of the use of unmanned aerial vehicles, due to bureaucratic and corruption schemes as well as the negative impact on objects of special use regime.Keywords: unmanned aerial vehicles, a temporary order of use of the airspace of Ukraine, Earth remote sensing, land management.